Dampak Implementasi Mesin Pencacah Rumput pada Keberlanjutan Perekonomian Kelompok Ternak Rojokoyo Tentrem - Unung Lesmanah; Cepi Yazirin; Nurul Humaidah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The population in Indonesia engages in entrepreneurship, particularly in livestock farming, with a focus on goats. This community service initiative was conducted with a livestock group by implementing a grass chopper machine. The challenges faced include the need for understanding livestock management to improve productivity, a lack of technological development in feed production equipment, limited knowledge about hygienic and quality livestock, marketing to mobile buyers, and a high incidence of livestock illnesses. The goal of this initiative is to implement a grass chopper machine to enhance the productivity of the livestock group. The methods used in this activity include socialization, digital marketing training, livestock health management training, feed management technology training, and the design and construction of the grass chopper machine. The partners for this initiative are the Rojokoyo Tentrem Livestock Group in Sumberejo, Poncokusomo, Malang, consisting of 10 members. As a result, the partners now have a grass chopper machine that meets their needs, leading to a 30% increase in feed production, improved understanding of digital marketing, and a 40% increase in knowledge about livestock health management and feed management.